Book Review:Michael Panaretos, Chronicle (in russian),ed. M. Kriukov, introd.-comment. S. P. Karpov, R. Sukurov, St Petersburg 2019 - ΣΑΒΒΙΔΗΣ Αλέξιος Γ. Κ. (Byzantina Symmeikta, 2019)
Book Review:Michael Panaretos, Chronicle (in russian),ed. M. Kriukov, introd.-comment. S. P. Karpov, R. Sukurov, St Petersburg 2019